Non-uniform metamorphosis underlies different development trajectories in hatchery-reared flathead grey mullet (Mugil cephalus) - Oz, Itay; Gajbhiye, Deodatta S.; Columbus-Shenkar, Yaara Y.; David, Lior; Golan, Matan (Frontiers in Marine Science, 2022)
The flathead grey mullet (Mugil cephalus) is at the focus of an intense domestication effort. However, despite significant advances, aquaculture of grey mullets is still based on capture of wild fingerlings in estuaries and stocking them into ponds. Such reliance on wild seed limits aquaculture production since it is highly seasonal, unpredictable, hinders genetic improvement programs and may negatively affect local capture fisheries. As captive breeding has been optimized for the species, to date, larval rearing remains the main challenge hindering the commercial production of captive-bred mullets. Here we set out to characterize larval development of grey mullets under captive conditions and to identify key developmental bottlenecks. By analyzing four larval batches from a commercial hatchery, we defined ten distinct developmental stages from hatching to the end of metamorphosis based on macroscopically observable morphological features. Using this developmental atlas to study development dynamics, we found that mullet larvae exhibit a biphasic growth profile with a 17-fold increase in growth rates at the onset of metamorphosis. Moreover, we found that within rearing batches, size variation almost doubles at metamorphosis, suggesting that the onset of metamorphosis is a critical step that increases variation by dictating different growth trajectories to early and late-metamorphosing larvae. By plotting the developmental stages against different morphometric parameters, we show here that age is a poor predictor of larval development due to large variations in development rates both within and between batches. We found that mullet larvae begin metamorphosis at a set size threshold of ~4.5 mm, however age at this threshold varies greatly even within batches. This age and size variance is further amplified by the aforementioned enhanced growth rates at metamorphosis and results in highly non-uniform fry, which complicate the rearing and weaning procedures. Understanding and treating the underlying causes for delayed metamorphosis are therefore considered important steps for the full domestication of the grey mullet.